A Randomized Controlled Trial Testing the Efficacy of the Creating Opportunities for Parent Empowerment Program for Parents of Children With Epilepsy and Other Chronic Neurological Conditions. Issue 3 (June 2016) - Duffy, Lisa V.; Vessey, Judith A.
Abstract : Abstract: Background: Parents of children with epilepsy and other neurological conditions live with a feeling of constant uncertainty. The uncertainty associated with caring for a child with a neurological condition produces stress, which leads to decreased parental belief in caregiving skills, anxiety, and depression, ultimately altering parental functioning resulting in an increase in child behavioral problems. The stress associated with caring for children with neurological conditions is unlike caring for children with other chronic conditions. Neurological conditions are unpredictable, and there are often no warning signs before an acute event. This unpredictability accompanied with stigma results in social isolation and impacts family functioning. In addition, children with neurological conditions have a higher rate of psychological comorbidities and behavior problems when compared with children with other chronic conditions. This produces an additional burden on the parents and family.Study Design: This randomized controlled trial tested the efficacy of the Creating Opportunities for Parent Empowerment intervention for parents of children with epilepsy and other neurological conditions. This intervention was administered at three intervals: (a) during hospital admission, (b) 3 days after hospital discharge by telephone, and (c) 4–6 weeks after hospital discharge.Results: Forty-six parents of children admitted to the inpatient neuroscience unit at Boston Children's Hospital participated in the study. Several study limitations resulted in an inadequate sample size to obtain the power necessary to reach statistically significant results for most of the research questions. A one-between, one-within multivariate analysis of variance revealed that the main effect of time was significant for differences in state anxiety for both the usual care group and the intervention group, F (1, 20) = 9.86, p = .005, indicating that state anxiety for both groups combined was more pronounced during the hospitalization. A one-between, one-within multivariate analysis of variance showed that the effect of the interaction between time and group was significant for internalized behavior assessment system score only ( p = .037) because the usual care group reported a significant decrease in internalizing behavior scores in their children over time.Conclusions: Findings from this study have significant implications for clinical practice and future research. Parents of children with neurological conditions often struggle to manage a constant feeling of uncertainty in their daily lives. Nurses possess the knowledge and expertise necessary to identify the psychosocial needs of these parents and provide education and support as needed. Future research should focus on designing interventions to meet the needs of these families and develop strategies to help improve the quality of life for both the parent and child living with a neurological condition.